Gentle treasures stories of women against mining in the Philippines - Alyansa Tigil Mina; Pasimio, Judy; Garingan, Edel; Sevilla, Farah (Quezon City Alyansa Tigil Mina/HARIBON Foundation, 2012)
This compilation gives honor to all women who continue to campaign for human dignity, biodiversity conservation and sustainable communities. To them who do not allow mining projects destroy their rich land and the beautiful future they are preparing for the next generation.
UCWS-2960g donated by Akbayan Party List.
Keywords: Mineral industries -- Philippines; Mines and mineral resources -- Philippines; Women -- Political activity -- Philippines